Realistic simulation analysis and performance testing of one KW fuel cell powered three-wheeler - Anandkumar Gunasekaran; Ramakrishnan Sambasivam; Anbuchezian Ashokan; Dhileepan Sekar; Silambarasan Rajendran; Ruby Pant (Results in Engineering)
In order to provide a sustainable, emission-free urban transportation option, this study offers a thorough design, modeling, and experimental validation of a fuel cell electric three-wheeler driven by a 1 kW Proton Exchange Membrane Fuel Cell (PEMFC). An intelligent switchover mechanism controlled by real-time monitoring via an Arduino-based control system guarantees continuous operation in a hybrid configuration that incorporates a lithium iron phosphate (LiFePO₄) battery. MATLAB Simulink was used to characterize the PEMFC stack for important metrics including hydrogen consumption, stack efficiency (up to 60 %), and I-V behavior. In order to evaluate system-level dynamics and optimize powertrain response under various load situations and real-world driving cycles, a digital twin of the vehicle was created in Simcenter Amesim. At a maximum speed of 46 km/h, experimental trials showed dependable vehicle propulsion; depending on the speed, the hydrogen consumption varied from 8 to 13 L during 5 min periods. Despite hydrogen's lower volumetric energy density, the vehicle's performance was further compared to diesel and electric versions, demonstrating competitive fuel economy and energy efficiency. Notably, reliable energy management and vehicle control were guaranteed by the combination of a BLDC motor, a high-efficiency DC-DC converter, and real-time voltage monitoring. This study provides a useful step toward decarbonized urban mobility infrastructures by confirming the viability of low-power fuel cell mobility solutions for short-distance, emission-free transportation.